Odstąpienie od wymierzenia kary lub środka karnego w prawie karnym skarbowym - Czichy, Krzysztof (Kwartalnik Prawa Publicznego, 2015)
The Legislator have provide a number of institutions that enable adjustment of the penal reaction to the circumstances of case and characteristics of perpetrator. One of the institutions is the possibility to renounce of punishing or using the punitive measures. Fiscal Penal Code making that institution does not refer to regulations of Penal Code, but makes own, autonomous regulation in this matter. Introduced publication present not only premises and the process of its use, but also tries to answer question about the frequency of its usage.